Analysis of partial trade credit financing in a supply chain by EOQ-based inventory model for exponentially deteriorating items. (1st January 2012) - Mahata, Gour Chandra
In the classical inventory (or) supply chain models, it was assumed that the retailers and their customers must pay for the items as soon as the items are received. However, in practice, the supplier usually is willing to provide the retailer a full trade credit period for payments and the retailer just offers the partial trade credit period to his/her customers. This paper develops economic order quantity-based inventory model to investigate the retailer's inventory policy for deteriorating items under two levels of trade credit in a supply chain management situation as a cost minimisation problem under partial trade credit option to their customers. Mathematical theorems, lemmas and algorithms are developed to efficiently determine the optimal inventory policy for the retailer. We deduce some previously published results of other researchers as special cases. Finally, numerical examples are given to illustrate the theorems and obtain a lot of managerial phenomena.